Efeito do calçado nas variáveis dinâmicas e cinemáticas do salto contramovimento de atletas de atletismo sub 18 - Luíza Stephanie Tavares (2023)
The countermovement jump (SCM) is commonly used in sports as a significant performance parameter that can be influenced by various factors, such as footwear. The objectives of this research were twofold: 1. to compare various methods for calculating the maximum jump height (Hmáx) in the context of the SCM. These methods included vertical center of mass (CM) displacement analysis through 3D motion capture (CMAV), CM displacement through double integration of ground reaction force (DIFR), impulse-momentum (IM), work-energy (TE), and flight time (TV). 2. To evaluate the influence of footwear on the dynamic and kinematic variables associated with SCM. The dynamic variable calculations involved the use of two triaxial AMTI® force platforms (1000Hz) and the synchronization of 11 Optitrack® system cameras (200Hz) integrated with Motive MTV-BDY image analysis software. These tools captured 3D coordinates of 30 markers affixed to the trunk and lower limbs of 15 active athletes engaged in various track and field disciplines (mean age: 16.5±1.2 years; mean body mass: 60.01±6.66 kg; mean height: 1.7±0.09 m). This facilitated the acquisition of kinematic variables. Each athlete performed six SCM attempts, alternating between wearing and not wearing shoes. Variables such as Hmáx, peak force, peak rate of force development (TDFm), symmetry angle (θ), and angular range of motion of the hip, knee, and ankle joints were extracted from force-time curves and CM trajectories. Means, standard deviations, and coefficients of variation (CV) were calculated for these variables. The normality of the dynamic and kinematic data was assessed using the Lilliefors statistical test. The comparison of Hmax calculations using different methods involved the use of SCMs performed both with and without shoes. The Bland-Altman test (p<0.05) was separately applied to each attempt. To assess symmetry between limbs and the influence of footwear, paired t-tests were conducted (p<0.05). The CMAV method demonstrated a lower CV compared to the other methods. The TV method exhibited a higher correlation and a smaller bias when compared to CMAV, relative to the other methods. Hmáx values calculated using the CMAV and TV methods did not significantly differ in the second (p=0.27) and third (p=0.22) attempts. In terms of footwear's impact, only peak force exhibited significant differences, being higher with footwear (p = 0.0019). The symmetry angle (θ) was observed to be closer to zero for all variables, regardless of footwear, indicating symmetry between the right and left limbs. In conclusion, the CMAV method is the most suitable, as it is a direct measurement method, free from inference or estimation, thereby eliminating the need for models and calculations. However, the TV method can be a viable alternative when CMAV isn't feasible, as it demonstrated no significant differences among itself in most trials. Furthermore, footwear had negligible effects on the symmetry of lower limbs, the majority of dynamic variables, and kinematics.